Pengaruh Pertumbuhan Laba dan Dana Syirkah Temporer terhadap Maqashid Syariah pada Bank Umum Syariah Periode 2021-2023 - Nurhayati, Sri; Sidi, Yudi Priambodo Purnama; Harris, Allan (Sekolah Tinggi Ilmu Ekonomi Syariah (STIES) ALIFA, 2025)
The purpose of the study was to see the effect of profit growth and temporary syirkah funds with Maqasyid Syariah in 2021-2023. Maqasyid Syariah can be interpreted as ownership of a company that can be seen from the value of its shares. While Bank Umum Sariah can be interpreted as a bank that operates based on Sharia principles and all its operations are based on the Quran and Hadith and there is a halal guarantee in its transactions. The methods used are quantitative verification and descriptive. With a total sample of 24. The results of this study are the Probability Value of X1 (Profit Growth) > 0.5 with a Coefficient value of -0.0001, meaning that the variable X1 (Profit Growth) has no effect on Maqasyid Syariah. The Probability Value of X2 (Temporary Syirkah Funds) <0.5 with a Coefficient value of 1.02E-08 means that the variable X2 (Temporary Syirkah Funds) has an effect on Maqasyid Syariah. The F-statistic value <0.05, meaning that simultaneously or together, variables X1 and X2 have an effect on Maqasyid Syariah. The R-squared value is 0.879 or 87.9%, meaning that variables X1 and X2 are able to provide an influence of 87.9% on Maqasyid Syariah. The rest is influenced by other factors